The Recovery of Factor VIII from Fresh-Frozen, Indated and Outdated Human Plasma - Whitman, Daniel E.; Switzer, Mary Ellen; McKee, Patrick A. (Thrombosis and Haemostasis, 1976)
The availability of factor VIII concentrates is frequently a limitation in the management of classical hemophilia. Such concentrates are prepared from fresh or fresh-frozen plasma. A significant volume of plasma in the United States becomes “indated”, i. e., in contact with red blood cells for 24 hours at 4°, and is therefore not used to prepare factor VIII concentrates. To evaluate this possible resource, partially purified factor VIII was prepared from random samples of fresh-frozen, indated and outdated plasma. The yield of factor VIII protein and procoagulant activity from indated plasma was about the same as that from fresh-frozen plasma. The yield from outdated plasma was substantially less. After further purification, factor VIII from the three sources gave a single subunit band when reduced and analyzed by sodium dodecyl sulfate polyacrylamide gel electrophoresis. These results indicate that the approximately 287,000 liters of indated plasma processed annually by the American National Red Cross (ANRC) could be used to prepare factor VIII concentrates of good quality. This resource alone could quadruple the supply of factor VIII available for therapy.